2016
DOI: 10.1111/apt.13873
|View full text |Cite
|
Sign up to set email alerts
|

Letter: proton pump inhibitors and prognosis of cirrhosis – searching for the balance point

Abstract: Linked Content This article is linked to Dultz et al paper. To view this article visit https://doi.org/10.1111/apt.13061.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The elevated risk of HE for PPI users was consistent regardless of the study design, definition of PPI use, study location, type of advanced liver disease, and outcomes analyzed. Previous studies revealed that HE was a predictor of PPI therapy[26,27], which suggests that the elevated risk of HE for PPI users may be affected by confounding by indication. However, the sensitivity analysis focusing on patients without past HE episodes showed a similar result.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated risk of HE for PPI users was consistent regardless of the study design, definition of PPI use, study location, type of advanced liver disease, and outcomes analyzed. Previous studies revealed that HE was a predictor of PPI therapy[26,27], which suggests that the elevated risk of HE for PPI users may be affected by confounding by indication. However, the sensitivity analysis focusing on patients without past HE episodes showed a similar result.…”
Section: Discussionmentioning
confidence: 99%
“…The developed practical guidance is based on information from the product information (Table ) and data extracted from 69 articles included in the literature review (Figure ) . Twelve of the included studies focused on pharmacokinetics (Table ), 51 on safety, and six studied both safety and pharmacokinetics of PPIs.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐seven articles studied the safety of PPIs as a group in patients with cirrhosis (Table S1) . These studies mostly focused on the risk of spontaneous bacterial peritonitis or infections in general.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations